The process of collecting and evaluating evidences for the development of Guidelines for the management of rheumatoid arthritis, Japan College of Rheumatology 2014: Utilization of GRADE approach. Issue 2 (3rd March 2016) - Kojima, Masayo; Nakayama, Takeo; Kawahito, Yutaka; Kaneko, Yuko; Kishimoto, Mitsumasa; Hirata, Shintaro; Seto, Yohei; Endo, Hirahito; Ito, Hiromu; Kojima, Toshihisa; Nishida, Keiichiro; Matsushita, Isao; et al.
Abstract : Objectives. To describe the process of collecting and evaluating evidence for treating rheumatoid arthritis (RA) for developing clinical practice guidelines (CPGs) for rheumatologists in Japan. Methods. The task force comprised rheumatologists, epidemiologists, health economists, and patients. First, the critical outcomes were determined according to a three-round Delphi method, and eight topics with 88 clinical questions (CQs) were formulated. A systematic review of CQs was conducted using the Cochran Database of Systematic Reviews, MEDLINE, and Japana Centra Revvo Medicina (2003–2012). A questionnaire survey and focus group interview were performed to capture the patients' values and preferences. Data from the National Health Insurance drug price list and product information provided by pharmaceutical companies were collected to evaluate drug cost and safety. The GRADE approach was used to describe the evidence quality and determine the strength of recommendations. Recommendations were developed using a modified Delphi method by a multidisciplinary panel including patients. Results. Eight meetings and frequent e-mail communications were conducted to draft a quality assessment of evidence and recommendations. For 88 CQs, recommendation statements were determined. Conclusions. Using the GRADE approach, new CPGs successfully addressed important clinical issues for treating RA patients. Timely updating of recommendations should be routinely considered.